2000
DOI: 10.1021/ac990994f
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Thermoresponsive Poly(N-isopropylacrylamide-co-acrylic acid) Hydrogels:  Studies with Electroactive Probes

Abstract: A new method of preparing thermoresponsive hydrogels consisting of N-isopropylacrylamide (NIPA) and acrylic acid (AA), with a well-defined concentration of an electroactive probe, 1,1'-ferrocenedimethanol (Fc(MeOH)2), is described, and a comparison of the physical and electrochemical properties of NIPA-AA gels with those of aqueous solutions is presented. The NIPA-AA gels undergo a discontinuous volume phase transition at 45 degrees C; this transition results in a release of approximately 40% of the solution m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 22 publications
3
70
0
Order By: Relevance
“…Only small difference, approximately 16%, is observed between diffusion coefficients of Fc(MeOH)2 in solutions and NIPA-AA gels. This behavior has been reported previously for swollen gels [8,15], and an appropriate model for the description of transport of small molecules in polymeric gels has been proposed [8]. No difference can be seen between systems with and without electrolyte; since Fc(MeOH)2 is an uncharged probe, there are no electrostatic interactions between the gel network and the uncharged electroactive probe.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…Only small difference, approximately 16%, is observed between diffusion coefficients of Fc(MeOH)2 in solutions and NIPA-AA gels. This behavior has been reported previously for swollen gels [8,15], and an appropriate model for the description of transport of small molecules in polymeric gels has been proposed [8]. No difference can be seen between systems with and without electrolyte; since Fc(MeOH)2 is an uncharged probe, there are no electrostatic interactions between the gel network and the uncharged electroactive probe.…”
Section: Resultssupporting
confidence: 81%
“…4, and are presented in Table 3. Similarly to FcTMA + and Fc(MeOH)2 [8,15], there are no significant differences in £ a -values for the probe ions between gels and an aqueous solution.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Recently, we have shown that steady-state voltammetry at microelectrodes is extremely convenient for the determination of some important parameters characterizing the transport properties of gels. [9][10][11][12][13] These include diffusivities of probe molecules, local gel viscosity, and activation energy of transport.…”
Section: Introductionmentioning
confidence: 99%